Tanzania climate-smart agriculture program - Ministry of Agriculture, Food Security and Cooperatives (2015)
In Sub-Saharan Africa, heavy reliance on rain-fed agriculture renders farming communities more vulnerable to effect of climate change and variability resulting in widespread food insecurity and poverty. Climate change and variability present new challenges particularly for smallholder farmers whose main stay is agriculture. Providing food for the future will require a holistic approach in order to produce on less land and by using appropriate methods. Farming communities and researchers are obliged to re-evaluate mainstreaming of farming practices and techniques and look for ways of securing food through adoption of conservation agriculture, integrated livestock keeping, fish farming and agro-forestry. High dependence on rain-fed agriculture and poor soil health increases vulnerability of farming systems and predisposes rural households to food insecurity and poverty thus eroding their productive assets and weakening their coping strategies and resilience to external shocks. Increasingly, the onset, duration and intensity of rains vary considerably from year to year, while the frequency and intensity of extreme weather events such as drought and floods are on the increase with devastating impacts on the national economy and the livelihoods of the people. Moreover agricultural seasons in some areas of the country are expected to shift. Drastic and innovative measures are therefore needed to help farmers and consumers cope with the changes in emerging and projected weather patterns.